(untitled) (Asian Education Studies, 2026)
This paper takes into consideration of the problems discovered in the quality of online course teaching in the University and cooperates with related departments to conduct a survey on quality of online course teaching and practice, with the purpose of detecting how students evaluate their online course teaching and learning at present, analyzing the factors that influence the online teaching quality, and proposing some strategies to facilitate and improve online evaluation of teaching and enhance education and teaching quality in the University.